ANALISIS PENGARUH PERTUMBUHAN GDP, INFLASI, BI RATE DAN NILAI TUKAR TERHADAP KREDIT BERMASALAH PADA BANK KONVENSIONAL DAN BANK SYARIAH - Silvia Eka Febrianti; Khusnul Ashar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Indonesian Banking use Dual-Banking System since the enactment of UU no. 7 in 1992 and UU no. 10 in 1998. Credit or Lending by conventional banks and syaria banks will always carry the credit risk or Non Performing Loan (NPL) and Non Performing Finance (NPF). NPL and NPF can be caused by banks external and internal factors. This Research attempts to identify the effect of external factors (macroeconomic variables) to NPL in conventional banking and NPF in syaria banking. Macroeconomic variables used in this research are GDP growth, Inflation (CPI ), BI Rate, and Exchange Rate. By using Error Correction Model (ECM), the results showed that in short term, only Exchange Rate that has a significant effect in NPL conventional banks and all independent variables have no effect in NPF syaria banks. In the Long term, GDP Growth, Inflation (CPI), BI Rate, and Exchange Rate have significant effect on the NPL conventional banks. However, only BI Rate that has significant effect on NPF syaria banks in the long term. Key Words: NPL, NPF, Conventional Bank, Syaria Bank, ECM